(untitled) (Experimental biology, 2022)
This paper presents the ecological and phytocenotic characteristics and state of the rare plant cenopopulation (CP) of the State National Nature Park "Burabay". The purpose of the scientific research is to study the current state of the cenopopulation of rare and endangered plants of the national park. Researches of the rare species’ cenopopulation of the national park were carried out by route reconnaissance method according to the generally accepted geobotanical methods. Locations and ecological and phytocoenotic indicators of 8 rare plant species were identified in the flora of the studied area. The populations of Cypripedium calceolus, Drosera rotundifolia and Tulipa patens cause the highest concern of possible extinction in the territory of SNPP "Burabay". The data obtained can be used in monitoring the state of the population of rare plant species in SNPP "Burabay" and for the development of the regional Red Data Book of Akmola region.